PRECISE MEANING OF A WORD THROUGH NUMBER UNDERSTANDING: INTRODUCTION - Elim, Hendry Izaac; Rajan, Jose (Pattimura University, 2023)
An introduction of a novel approach that can translate the meaning of a word in different language exactly. The method was used by employing a simple logic of number summation through the conversion of alphabet of a language into a number. The understanding of precise meaning of a word is shown from 2 different languages and alphabets to three types of languages. In addition, it was invented that it is also possible to have accurate synonym of a word in 4 kinds of languages. This simple technique suggests that by explaining the understanding and meaning of a word in number, the scholars can obtain exact similarity from a word.